Hubungan antara tingkat kecemasan akibat covid-19 dengan persepsi ketidakcukupan dalam pemberian asi : The relationship between the level of anxiety due to covid-19 and the perception of inventory breastfeeding - Liliana, Anita; Muflih, Muflih; Cahyanti, Anisa (Stikes Wira Medika Bali, 2021)
Psychological disorders in mothers cause reduced breastfeeding expenditure. Because it will inhibit the let down reflex. Maternal anxiety is increasing with the existence of social restrictions, so that the mother is worried that the child's needs cannot be met. and the mother said she was worried and confused about the current state of the Covid-19 pandemic. The purpose of this study is whether there is a relationship between the level of anxiety due to Covid-19 and the perception of adequacy in breastfeeding. The purpose of this study is whether there is a relationship between the level of anxiety due to Covid-19 and the perception of adequacy in breastfeeding. This type of research is a quantitative study and uses an analytical research design with a cross sectional approach. The subjects of this study were postpartum mothers who had babies. The object of this research is the level of anxiety due to covid-19. The location of this research was conducted at RSIA AMC Metro Lampung and the time of this research will be conducted in July - August 2020. Results of the study It is known that out of 33 respondents, 9 (27.3%) were not categorized as respondents, with 24 (72.7%) categories of respondents. It is known that out of 33 respondents with a perception of adequacy gave positive breastfeeding 17 (51.5%) respondents, and 16 respondents (48.5%) with a perception of adequacy. There is a significant relationship between the level of damage caused by Covid-19 and the perception of breastfeeding adequacy. (p-value 0.017 OR 13.333). This research concludes that there is a relationship between the level of anxiety due to Covid-19 and the perception of adequacy of breastfeeding.